1965
DOI: 10.1073/pnas.53.6.1443
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the role of protein synthesis in the regulation of corticosterone production by adrenocorticotropic hormone in vivo.

Abstract: The primary event following the administration of adrenocorticotropic hormone (ACTH) is the immediate increase in steroid synthesis by the adrenal gland.1 Previous studies by numerous investigators suggested that this action of ACTH was the result of specific activation of enzymes.2' 3 However, studies showing that puromycin or chloramphenicol blocked the stimulation of corticosterone synthesis by ACTH suggested that protein synthesis was involved in this process.4 5 But

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
0

Year Published

1970
1970
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 351 publications
(108 citation statements)
references
References 22 publications
4
104
0
Order By: Relevance
“…If cyclic AMP is involved in ACTH action, thi~ lag could represent the time needed for accumulation of sufficient cyclic AMP to stimulate steroidogenesis. Alternatively, this time may be necessary for the operation of processes initiated by cyclic AMP, such as synthesis of the labile protein postulated by Garren [13]. The latter possibility is more likely, as addition of 5 mM cyclic AMP to ceils results in a time lag of about 3 min before corticosterone is produced [ 14].…”
Section: Methodsmentioning
confidence: 99%
“…If cyclic AMP is involved in ACTH action, thi~ lag could represent the time needed for accumulation of sufficient cyclic AMP to stimulate steroidogenesis. Alternatively, this time may be necessary for the operation of processes initiated by cyclic AMP, such as synthesis of the labile protein postulated by Garren [13]. The latter possibility is more likely, as addition of 5 mM cyclic AMP to ceils results in a time lag of about 3 min before corticosterone is produced [ 14].…”
Section: Methodsmentioning
confidence: 99%
“…The pregnenolone production in the adrenal mitochondria from ether-stressed animals is much greater than those from cycloheximide-treated animals. Cycloheximide treatment of rats is thought to block the production of a factor important in the control of the metabolism of cholesterol by adrenal mitochondria [3]. Calcium ions have been reported to be important in controlling cholesterol metabolism [6].…”
Section: Resultsmentioning
confidence: 99%
“…Trophic hormone action could provide this cholesterol by promoting the hydrolysis of cholesterol esters in cellular lipid droplets by cholesterol esterase [15]. The rapidly turning over factor [3] proposed to be involved in the control of adrenal steroidogenesis probably does not promote transport of cholesterol into the mitochondrion. Adrenal mitochondria isolated from ether-stressed rats contain less cholesterol (16.0 nmol/ mg protein) compared to those obtained from cycloheximide-treated animals (27.0 nmol/mg protein) but the former mitochondria are capable of producing more pregnenolone in the presence of exogenous cholesterol ( fig.l).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that this mechanism is dependent on a cycloheximide-sensitive and highly labile protein which is rapidly synthesized on stimulation of steroidogenic cells (3)(4)(5). Among the leading candidates for such a pivotal protein factor is Steroidogenic Acute Regulatory protein (STAR) described by Orme-Johnson and Stocco (6,7) which has been shown to fulfill all the criteria predicted for the regulatory protein (reviewed in (ref.…”
Section: Vol 45 No 1 1998mentioning
confidence: 99%